Circumcision in Early Islam - Carmeli, Yehonatan ca. 20./21. Jh. (Der Islam, 2022)
The article asserts that verses 124-130 in the second sūrah of the Qurʾān (al-Baqara/"The Cow") alludes to the biblical precept (Genesis 17) but presents the practice as a custom that has no special virtues, and certainly not those the Jews ascribed to it. It then claims that circumcision is identified as one of Abraham's trials, which are mentioned in the Qurʾān and thus part of early Islam, and that this idea did not arise in the Middle Ages.